High-throughput UAV-based rice panicle detection and genetic mapping of heading-date-related traits - Chen, Rulei; Lu, Hengyun; Wang, Yongchun; Tian, Qilin; Zhou, Congcong; Wang, Ahong; Feng, Qi; Gong, Songfu; Zhao, Qiang; Han, Bin (Frontiers in Plant Science, 2024)
Rice (Oryza sativa) serves as a vital staple crop that feeds over half the world's population.Optimizing rice breeding for increasing grain yield is critical for global food security. Headingdate-related or Flowering-time-related traits, is a key factor determining yield potential. However, traditional manual phenotyping methods for these traits are time-consuming and labor-intensive.Here we show that aerial imagery from unmanned aerial vehicles (UAVs), when combined with deep learning-based panicle detection, enables high-throughput phenotyping of heading-daterelated traits. We systematically evaluated various state-of-the-art object detectors on rice panicle counting and identified YOLOv8-X as the optimal detector. Applying YOLOv8-X to UAV time-series images of 294 rice recombinant inbred lines (RILs) allowed accurate quantification of six headingdate-related traits. Utilizing these phenotypes, we identified quantitative trait loci (QTL), including verified loci and novel loci, associated with heading date. Our optimized UAV phenotyping and computer vision pipeline may facilitate scalable molecular identification of heading-date-related genes and guide enhancements in rice yield and adaptation.